Analysis Implementation Gamification Massive Open Online Course for Student Motivation Learning - Budi Harijanto; Meyti Eka Apriyani; Elok Nur Hamdana; Figha Al Azmi (Nusantara Science and Technology Proceedings, 2022)
The State Polytechnic of Malang has created a learning system that uses gamification as one method to improve student motivation in their academic work. Massive Open Online Courses, or MOOCs for short, are one of the learning strategies used. They are open to everyone and offer online learning opportunities with no cap on the number of students who can enroll. Gamification has been implemented in the State Polytechnic of Malang MOOC system for teaching web programming design to overcome concerns with the online learning system. To make learning more interesting and motivating, the MOOC system implements the concept of gamification. Research and development (R&D) techniques were employed in this study to validate the gamification design process. The study was conducted using two types of scenarios to test the level of student motivation from the use of MOOCs. Using gamification and MOOC is a new phenomenon in open learning and is known as a good strategy di Independent Campuses. Gamification consists of the show that badges, leader boards, and performance graphs positively affect competence need satisfaction. The calculation of the change in motivation is obtained by the activeness of students in answering quizzes, uploading the results of the Job sheet, and claiming rewards in each activity. The reward is one of the important points in gamification that can be used as a parameter to increase student motivation in studying any given material.